Analisis Usaha Arang Batok Kelapa pada UMKM Kamurang di Kabupaten Bandung - Febriyanto, Feri (Ma'soem University, 2025)
Coconut shell charcoal is a product derived from the processing of coconut shell residues that has financial value and is environmentally friendly. In addition to being used as an alternative fuel and planting medium, this charcoal is also a raw material for the production of activated carbon. The aim of this research is to analyze expenses, income, and profits; calculate the R/C ratio; and determine the break-even point for each production process in the coconut shell charcoal agroindustry at the Kamurang SMEs in Sukamulya Village, Rancaekek District, Bandung Regency. This study was conducted using a quantitative descriptive method with a case study approach. The data collection process was conducted through purposive direct question and answer sessions, observation of activities in the field, and forms given to business owners. From the data processing results, the total expenditure in the production process reached IDR 3,220,766.29 for one production cycle, with revenue of IDR 3,963,750 and profit of IDR 742,983.71. The R/C ratio is 1.23, which means that the business has a positive prospect for operation. The break-even point for revenue is IDR 174,636.1, the break-even price is IDR 6,134.79, and the break-even production points are 113.67 kg for large size, 193.24 kg for medium size, and 123.88 kg for small size. These findings indicate that coconut shell charcoal businesses have the potential to be developed as profitable and sustainable small-scale agro-industries.